KAJIAN HUBUNGAN FOSFAT AIR DAN FOSFAT SEDIMEN TERHADAP PERTUMBUHAN LAMUN Thalassia hemprichii DI PERAIRAN TELUK AWUR DAN PULAU PANJANG JEPARA - Setiawan, Dedi; Riniatsih, Ita; Yudiati, Ervia (Departemen Ilmu Kelautan, Fakultas PerikanJurusan Ilmu Kelautan, Universitas Diponegoro)
Seagrass growth is limited by the supply of nutrients such as nitrogen and phosphate particulates that serve as energy for photosynthesis. The magnitude of the role of phosphate in the metabolism and growth of seagrass Thalassia hemprichii important to serve as a study to determine the relationship of nutrients to the growing rate of seagrass in Teluk Awur and Pulau Panjang Jepara. The purpose of this study was to determine the concentration of phosphate in the water and sediment in the waters of the Teluk Awur and Pulau Panjang and its relation to seagrass leaf growth rate of T. hemprichii. The study was conducted in April - July 2012 includes literature studies, site surveys, field data collection and analysis of samples. Analysis of the relationship phosphate concentration on the rate of growth of seagrass T. hemprichii using bivariate correlation analysis. The results showed that the average growth rate - the average seagrass highest type T. hemprichii found in Teluk Awur on 8 week (0.81 cm/day). Meanwhile, the lowest growth rate found in Teluk Awur at week 2 (0.14 cm/day). The content of phosphate concentration of water in the Teluk Awur ranged from 0.009 to 0.028 mg/L and in Pulau Panjang ranged from 0.012 to 0.025 mg/L. The concentration of phosphate sediments in the Teluk Awur ranged from 20.870 to 23.250 mg/kg and Pulau Panjang 25.650 to 27.190 mg/kg. Relations water phosphate concentration and phosphate sediments to seagrass leaf growth in Teluk Awur are not considered closely related ,instead phosphate water to the growing rate of seagrass in Pulau Panjang is low and phosphate sediments to seagrass growth as very closely.